The new normal: bank lending and negative interest rates in Austria - Marcel Barmeier (Oesterreichische Nationalbank (OeNB), 2022)
Evidence on the effects of negative interest rates on bank lending is inconclusive so far. By applying a difference-in-difference estimation using granular loan level data with a large coverage from Austria, I show, contrary to some previous ndings, that the introduction of a negative deposit facility rate by the European Central Bank led to an increased credit supply by high-deposit nanced banks. Given the importance of relationship banking, the extended credit is granted mainly by smaller banks and via existing credit relationships to firms and households. Banks lend more often to indebted customers and to clients with higher probabilities of default, confirming the previous found increased risk-taking behavior in negative interest rate environment.
Keywords: E44; E51; E52; E58; G21; 330; Monetary policy transmission; negative interest rate policy; portfolio rebalancing channel; bank lending; nancial stability